2022
DOI: 10.3390/kidneydial2010005
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Vascular Access Dysfunction Occur despite Brachial Artery Blood Flow Being Higher than Preset Blood Flow?

Abstract: Background: In recent years, many reports have investigated the usefulness of brachial artery blood flow (BAF) measured by ultrasonography as an evaluation index for the vascular access (VA) stenosis of hemodialysis patients. However, the mechanism of VA dysfunction, despite BAF being higher than the preset blood flow, has not been clarified to date. Methods: The relationship between actual blood-removal flow and recirculation rate with decreasing VA flow was examined using a VA flow path model and pure water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Ono et al stated that it is important to focus on the blood flow waveform pattern rather than just the average shunt blood flow value to explain the shunt dysfunction from the verification using the experimental circuit. In addition, they speculated that recirculation or decreased actual blood removal flow would occur when the diastolic shunt flow falls below the set blood flow [16]. This study revealed that higher recirculation was observed in the diastolic phase, which has slower blood flow.…”
Section: Discussionmentioning
confidence: 78%
“…Ono et al stated that it is important to focus on the blood flow waveform pattern rather than just the average shunt blood flow value to explain the shunt dysfunction from the verification using the experimental circuit. In addition, they speculated that recirculation or decreased actual blood removal flow would occur when the diastolic shunt flow falls below the set blood flow [16]. This study revealed that higher recirculation was observed in the diastolic phase, which has slower blood flow.…”
Section: Discussionmentioning
confidence: 78%